Penentuan Rute Distribusi Menggunakan Metode Savings Matrix dengan Algoritma Nearest Insert, Nearest Neighbour, dan Farthest Insert pada UMKM Peralatan Plastik - Juniory Halim; Rainisa Maini Heryanto; David Try Liputra (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
Consumer satisfaction with a product could be determined based on several factors including quality, price, and fast distribution. Distribution activity is one of the important activities because it guarantees that products are circulated properly, do not accumulate in warehouses, and delivered on time. For micro, small and medium enterprises (MSMEs), distribution arrangements could provide significant savings in distance and distribution costs so as to increase profits. Besides that, distribution arrangements could also guarantee that products are delivered on time to consumers. This resarch uses a simple distribution determination method, the Savings Matrix method, followed by the Nearest Insert, Nearest Neighbour, and Farthest Insert heuristic algorithms. The purpose of this research is to help MSMEs that have the main distribution process to be able to arrange their distribution routes so that deliveries could be made on time and at minimal cost. In this research, a numerical example was used of a plastic equipment MSME which had problems with late delivery and the occurrence of round trips so that it became inefficient. In addition to determining the distribution route, four scenarios are also given for MSME to consider thus the distance and cost savings obtained are more significant. From the results of the calculation of determining the distribution route, it is found that the Savings Matrix method and the Nearest Neighbour heuristic method provide savings of around 12,82% or IDR 698,550 per month.